Penentuan Sifat Fisik Biji Kakao Varietas Klon 45 dan Sulawesi 01 di Kabupaten Bolaang Mongondow Utara - Febrianti Timumu; Ireine A. Longdong; Lady Ch. C. E. Lengkey (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2022)
The purpose of this study was to determine the dimensions of cocoa beans (length, width, thickness) and the average diameter of arithmetic, geometry, sphericity, porosity, density of kamba, angle of repose, and angle of friction of the clone varieties 45 and sulawesi 01. The method used in this research is the experimental method, analyzed descriptively. The results showed that the average cocoa beans of the Klon 45 variety were 27.25 mm long, 14.35 mm wide, 7.25 mm thick, arithmetic 16.28 mm, geometric 14.03 mm, sphericity 0.52. Sulawesi 01 variety, length 20.44 mm, width 12.29 mm, thickness 7.52 mm, arithmetic 13.46 mm, geometry 12.32 mm, sphericity 0.60. clone 45 variety had porosity of 30.62%, density of kamba 0.44 g/ml, weight of 100 seeds 95.39 g. The Sulawesi 01 variety has a porosity of 29.62%, a kamba density of 0.51 g/ml, a weight of 100 seeds 144.72 g. The angle of repose of the clone 45 variety is 29.96º at 9.19% moisture content and the Sulawesi 01 variety is 23.07º at 7.57% moisture content. The angle of friction for the clone 45 variety is 29.94º at 9.19% moisture content and Sulawesi 01 is 25.03º at 7.57% moisture content. Keywords: cocoa beans, physical properties, varieties.